Incidence of Treatment for End-Stage Renal Disease Among Individuals With Diabetes in the U.S. Continues to Decline - Burrows, Nilka Ríos (American Diabetes Association, 2010)
OBJECTIVE: We examined trends in incidence of treatment for diabetes-related end-stage renal disease (ESRD) in the U.S. RESEARCH DESIGN AND METHODS: Using the U.S. Renal Data System, we obtained the number of individuals having diabetes listed as primary diagnosis who initiated ESRD treatment between 1990 and 2006. Incidence was calculated using the estimated U.S. population with diabetes from the National Health Interview Survey and then was age adjusted based on the 2000 U.S. standard population. Trends were analyzed using joinpoint regression. RESULTS: The number of individuals who began diabetes-related ESRD treatment increased from 17,727 in 1990 to 48,215 in 2006. From 1990 to 1996, the age-adjusted diabetes-related ESRD incidence increased somewhat from 299.0 to 343.2 per 100,000 diabetic population (P = 0.45). However, from 1996 to 2006, the age-adjusted diabetes-related ESRD incidence decreased by 3.9% per year (P < 0.01) from 343.2 to 197.7 per 100,000 diabetic population. Among individuals with diabetes aged <45 years, diabetes-related ESRD incidence decreased by 4.3% per year (P < 0.01) from 1990 to 2006. Among older individuals, incidence increased during the 1990s but decreased in later years, by 3.9% per year (P < 0.01) among individuals aged 45–64, by 3.4% per year (P < 0.01) among individuals aged 65–74 years, and by 2.1% per year (P = 0.02) among individuals aged ≥75 years. CONCLUSIONS: Diabetes-related ESRD incidence in the diabetic population has declined in all age-groups, probably because of a reduction in the prevalence of ESRD risk factors, improved treatment and care, and other factors.